Post-traumatic stress disorders among children and adolescents in conflict-affected zones of Amhara region, February 2022 - Biset, Gebeyaw; Goshiye, Debrnesh; Melesse, Negesse; Tsehay, Mekonnen (Frontiers in Psychology, 2023)
Background: To date, conflict is causing extreme social crises worldwide. Children are the most vulnerable groups for trauma and violence in conflict ridden areas. Posttraumatic stress disorders (PTSDs) is the most widely reported psychological problem in the aftermath of conflict. However, less attention was given to children living in conflict areas of the world. Objective: This study was intended to assess posttraumatic stress disorders among children and adolescents in conflict affected zones of Amhara region from January to February 2022. Method: A community-based cross-sectional study was employed from January to February 2022. A multistage random sampling technique was employed to recruit the study participants. A structured interviewer-administered questionnaire was used to collect the desired data. Data was verified, coded, and entered into EpiData version 3.1 and analyzed using SPSS version 24 statistical software. Result: A total of 846 children with response rate of 94.33% were screened for trauma. Subsequently, 557 (69.80%) children had experienced trauma. Of these 557 children who experienced trauma, 203 (36.45%) develop post-traumatic stress disorders. Mass screening of children and adolescents for post-traumatic stress disorders and rehabilitation services like resilience trainings and psychosocial supports are recommended. Keywords: Conflict, post-traumatic stress disorder, Ethiopia, Amhara region.